Common bees of eastern North America - Messinger Carril, Olivia, 1976-; Wilson, Joseph S., 1980- (Princeton field guides., 2021)
"Bees play an essential role in the pollination of native plants and agricultural crops across the globe. In North America alone there are more than 4,000 bee species. In spite of their abundance and diversity there is no accessible field guide for the non-expert. This book will remedy that situation by providing a carefully crafted introduction to bee identification for eastern North America. No portable field guide could include coverage of the myriad species in the region, so the book concentrates on identifying bees at the genus level. It includes information on the 72 different genera that are found east of the Rockies. The introduction includes coverage of bee biology and anatomy, as well as a section on how to use the guide. For each genus, the book provides habitus (side) and dorsal (top) views, close-up photos of important features, field pictures, maps, descriptions of life history traits, and a description of the genus as a whole. The habitus and dorsal views are uniquely detailed, as they use a photography technique developed by researchers at the USGS Bee Inventory and Monitoring Lab. While the guide is primarily designed to allow the user to identify at the genus level, the authors provide features on six of the most common and easily identifiable species for each genus. While many field guides are ordered taxonomically, this book is organized by morphology to better aid the non-expert in making a correct identification"--